The Development of Handicraft Teaching Methods - Širiakovienė, Asta (Acta Paedagogica Vilnensia, 2001)
In Lithuania handicraft teaching methods were studied by the following scholars: V. Mikėnas, A Vaičiulienė, J. Jasaitis, A Zybartas, J. Galkauskas, V. Šidlauskienė, L. Statauskienė anei other. The goal of today’s school is to provide all–round education. Therefore, a teacher chooses such teaching methods that are best suited to achieve goals and tasks. Discussion, the method of out-of-school activities, questionnaire and teaching in groups are new and effective methods of handicraft teaching. The application of the new methods stimulates independent thinking and closer connections between a teacher and a pupil. In such a way, the pupil can reveal his personality. With respect to teaching methods, not all methods are equally valuable and objective. A teacher of handicraft has to choose the teaching methods keeping in mind the difference in pupils’ abilities and skills, cultural experience and education in various areas.